A Comparisons of How Indonesian Law and Texas Law Address Criminal Responsibility for Sexual Violence Offenders - Airiique Bintang Merah Harley; Kayus Kayowuan Lewoleba (Law Development Journal, 2025)
This study compares how criminal liability for sexual offenses is addressed in Indonesia and Texas through a normative analysis. Indonesia has shifted from its Dutch colonial legal background toward a victim-focused approach under Law No. 12 of 2022 (UU TPKS), which covers both non-physical and psychological abuse. In contrast, Texas relies on common law principles that stress consent, categorize offenses as felonies, and require offender registration. The research shows that Indonesia emphasizes restorative justice and uses wider definitions, while Texas prioritizes public safety with strict monitoring after convictions. These differences reflect distinct legal philosophies for dealing with sexual violence.